Enhanced fiscal integration in the EMU? Proceedings of the joint workshop, organised by the European Commission, the European Stability Mechanism and the German Council of Economic Experts (Luxembourg, 2018)
"This volume presents the proceedings of a workshop, where the fiscal policy architecture in Europe and its potential future developments were discussed."